2013
DOI: 10.1002/eji.201242983
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella polarises peptide‐MHC‐II presentation towards an unconventional Type B CD4+T‐cell response

Abstract: Distinct peptide-MHC-II complexes, recognised by Type A and B CD4+ T-cell subsets, are generated when antigen is loaded in different intracellular compartments. Conventional Type A T cells recognize their peptide epitope regardless of the route of processing, whereas unconventional Type B T cells only recognise exogenously supplied peptide. Type B T cells are implicated in autoimmune conditions and may break tolerance by escaping negative selection. Here we show that Salmonella differentially influences presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Alternatively, exogenous peptides were shown to bind to mature MHC II molecules in early endosomes or at the APC surface in the absence of functional H2‐DM, resulting in formation of a mixture of type A and type B T‐cell conformers . Infection of mice with Salmonella typhimurium has also been shown to bias HEL presentation by dendritic cells (DC) towards a type B T‐cell response by a Dectin‐1‐dependent mechanism . Furthermore, mice expressing endogenous HEL were used to show that type B T cells escape negative selection during thymic development in vivo , whereas the majority of type A T cells are deleted, creating a scenario in which self‐reactive type B T cells could persist in peripheral lymphoid organs.…”
Section: Introductionsupporting
confidence: 66%
“…Alternatively, exogenous peptides were shown to bind to mature MHC II molecules in early endosomes or at the APC surface in the absence of functional H2‐DM, resulting in formation of a mixture of type A and type B T‐cell conformers . Infection of mice with Salmonella typhimurium has also been shown to bias HEL presentation by dendritic cells (DC) towards a type B T‐cell response by a Dectin‐1‐dependent mechanism . Furthermore, mice expressing endogenous HEL were used to show that type B T cells escape negative selection during thymic development in vivo , whereas the majority of type A T cells are deleted, creating a scenario in which self‐reactive type B T cells could persist in peripheral lymphoid organs.…”
Section: Introductionsupporting
confidence: 66%
“…Several groups have shown that Salmonella inhibits surface presentation of MHCII (Cheminay et al., 2005, Halici et al., 2008, Jackson et al., 2013, Lapaque et al., 2009a, Mitchell et al., 2004). This was attributed to the SPI-2 T3SS (Cheminay et al., 2005, Mitchell et al., 2004) and the actions of several effectors that interfere with vesicular trafficking (Cheminay et al., 2005, Halici et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant strain analysis showed that several effectors affecting vesicular trafficking disrupt T cell proliferation (Cheminay et al., 2005, Halici et al., 2008). Another study revealed that in Salmonella- infected cells, surface levels of mMHCII are reduced through its ubiquitination (Jackson et al., 2013, Lapaque et al., 2009a). However, the effector(s) and mechanisms involved in the regulation of mMHCII ubiquitination are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Typhimurium results in an increase in presentation of exogenous peptide to type B T cells . The effect required direct contact between the bacteria and APC . To determine if the phenomenon was induced through recognition by PRRs, we exposed murine BMDCs to a panel of PAMPs and examined presentation to the type B T‐cell hybridoma, 11A10.…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium (HKST) led to reduced presentation of peptide and native Ag to type A T cells. Presentation of peptide to type B T cells was dramatically increased, but presentation of native Ag was negligible . Total levels of HLA‐DR and HLA‐DM were unaffected by exposure to S .…”
Section: Introductionmentioning
confidence: 99%